TOTAL SERUM PROTEIN AND CHOLESTEROL CONCENTRATIONS AT INDUCED AND NATURAL PUBERTAL OESTRUS IN INDIGENOUS HEIFERS - R. K. BISWAS2, B. K. SARMAH1 (Indian Journal of Animal Production and Management, 2017)
Twenty prepubertal indigenous heifers (Bos indicus) of Assam aged 18-24 months,weighing 67-90 kg were selected for hormonal induction of oestrus and to compare theserum levels of protein and cholesterol at induced and at natural pubertal oestrus. Another15 prepubertal indigenous heifers of similar age and body weight served as untreatedcontrol. Heifers were examined rectally to ensure that they had no corpus luteum and/oronset of oestrus before treatment. Each of the heifers was treated with Crestar injectioncontaining 3 mg norgestomet and 5 mg oestradiol valerate. Implant was removed on day 9of insertion and PMSG was administered @ 300 IU. Of 20 treated heifers induced tooestrus, 16 (80%) ovulated, 4 (20%) heifers did not ovulate. Heifers under control groupexhibited natural pubertal oestrus at an average age of 33.60 ± 2.81 months. Of these 10(66.67%) heifers ovulated while 5(33.33%) did not ovulate. Total serum protein concentrationin prepubertal heifers before treatment ranged between 7.20 ± 0.10 and 7.65 ± 0.18 g%.The pre-treatment level of total serum protein was lower in prepubertal heifers that did notovulate subsequently which was significant (P